Employing motion graphics videos in public awareness advertisements on social media platforms - Faten Ibrahim (Journal of Architecture, Art & Humanistic Science, 2023)
Abstract:The term "motion graphic" is very popular these days; Because it can be used in many areas, it is a unique communication method that enables you to mix several elements together, such as pictures, shapes, characters and sound effects, making the idea you present or the story enjoyable, and easy to understand. Various statistics have proven that Motion Graphics ads are the most widespread and the most widely used on various social media.Motion graphic video has several areas, and the research discussed the use of motion graphics in awareness advertisements in general and health awareness in particular, as health awareness represents one of the important challenges for the designer to persuade the audience to act differently from what they are used to in order to preserve their health first and for society secondly, and This is by trying to identify the reasons for using motion graphic art in health awareness advertisements through various studies that have linked the art of motion graphic art and awareness advertisements by identifying the characteristics of this new art and identifying its advantages and linking them to the characteristics of health awareness advertisements.The researcher dealt with two campaigns from the Facebook platform for a charitable organization, the Ahl Masr Foundation, which is provided by Ahl Masr Hospital for the treatment of burns free of charge, given that the various statistics proved that the Facebook platform is the most interactive platform by Egyptians, and the Ahl Masr Hospital for Burns is the first and largest hospital and research center To treat accident and burn victims free of charge in Egypt and the Middle East.The first campaign containing four ads, and the second five ads, and each of the two campaigns was first described and then analyzed for each of the elements used in the advertising film. Attempting to answer the research questions, and at the end of the research the researcher has reached the most important advantages of motion graphic art, which she strongly recommends for awareness advertisements, as it is characterized by the ability to attract attention and emotional capture. It can also present complex ideas in a simple visual way, making it easier to communicate with target audiences. The researcher also concluded that the visual elements used in the advertisement play a major role in the interaction and acceptance of the presented advertising message.